Linguistics Expression of Piety in XVI Century Polish Principle of St. Clare’s Convent. Virtue of Poverty as the Main Element of the Normative Act - Szagun, Dorota (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
This paper focuses on issues regarding history of use of the language, namely the way the languageis used to express the piety, characterizing a communication group of the Polish St. Clare’s Convent.The language material was extracted from XVI century Polish principle of St. Clare’s Convent and, onthe basis of the material, there was an attempt to reconstruct the meaning of poverty. As a result of lexical analysis of the vocabulary related to the virtue of poverty, which is a cardinal one for the Convent,a change in the meaning was proved and expressed in a normative act of the principle — in the directionof lack of personal property. Apart from non-language reasons of such a modification, the change is basedon detailed instructions, which regulate the life in the Convent, and, therefore, the specificity of type ofthe text.